Antimicrobial Resistance Profiling and Phylogenetic Analysis of Neisseria gonorrhoeae Clinical Isolates From Kenya in a Resource-Limited Setting - Juma, Meshack; Sankaradoss, Arun; Ndombi, Redcliff; Mwaura, Patrick; Damodar, Tina; Nazir, Junaid; Pandit, Awadhesh; Khurana, Rupsy; Masika, Moses; Chirchir, Ruth; Gachie, John; Krishna, Sudhir; et al. (Frontiers in Microbiology, 2021)
Africa has one of the highest incidences of gonorrhoea. Neisseria gonorrhoeae is gaining resistance to most of the available antibiotics, compromising treatment across the world. Whole-genome sequencing (WGS) is an efficient way of predicting AMR determinants and their spread in the population. Recent advances in next-generation sequencing technologies like Oxford Nanopore Technology (ONT) have helped in the generation of longer reads of DNA in a shorter duration with lower cost. Increasing accuracy of base-calling algorithms, high throughput, error-correction strategies, and ease of using the mobile sequencer MinION in remote areas is leading to its adoption, for routine microbial genome sequencing. To investigate whether MinION-only sequencing is sufficient for WGS and downstream analysis in resource-limited settings, we sequenced the genomes of fourteen suspected N. gonorrhoeae isolates from Nairobi, Kenya. Using WGS, the isolates were confirmed to be cases of N. gonorrhoeae, co-occurrence of N. gonorrhoeae with Moraxella oslonesis and N. meningitidis. N. meningitidis has been implicated in sexually transmitted infections in recent years. The near-complete N. gonorrhoeae genomes (n=10) were analysed further for mutations/factors causing AMR using an in-house database of mutations curated from the literature. We observe that ciprofloxacin resistance is associated with multiple mutations in both gyrA and parC. Mutations conferring tetracycline (rpsJ) and sulfonamide (folA) resistance and plasmids encoding beta-lactamase were seen in all the strains and tet(M)-containing plasmids were identified in nine strains. Phylogenetic analysis clustered the ten isolates into clades containing previously sequenced genomes from Kenya and countries across the world. Based on homology modelling of AMR targets, we see that the mutations in GyrA and ParC disrupt the hydrogen bonding with quinolone drugs and mutations in FolP may affect interaction with the antibiotic. Here, we demonstrate the utility of mobile DNA sequencing technology supplemented with consensus genome in sequence typing and elucidating the basis of AMR. The workflow followed in the study, including AMR mutation dataset creation and the genome identification, assembly and analysis, can be used for any clinical isolate. Further studies are required to determine the utility of real-time sequencing in outbreak investigations, diagnosis and management of infections, especially in resource-limited settings.